RJFA 2021
DOI: 10.7176/rjfa/12-14-03
|View full text |Cite
|
Sign up to set email alerts
|

Financial Knowledge and Retirement Planning among Pension Scheme Members in Kenya

Abstract: The rising cost of living, increasing life expectancy and high levels of old-age poverty in Kenya implies that many older people cannot afford necessities. Therefore, the need for individuals to plan for their future financial needs through planning for their retirement has become crucial. Unfortunately, most people who save for retirement in Kenya save with the National Social Security Fund (NSSF), which has a low replacement rate. Therefore, financial knowledge plays an indispensable role in influencing an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Grant, 1991) states that KBV identifies knowledge as the most resource of a firm whose strategic nature has important implications for competitive advantage. Stella, Florence, and Jane (2021) found that comprehensive retirement planners had high financial knowledge scores on basic financial concepts.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Grant, 1991) states that KBV identifies knowledge as the most resource of a firm whose strategic nature has important implications for competitive advantage. Stella, Florence, and Jane (2021) found that comprehensive retirement planners had high financial knowledge scores on basic financial concepts.…”
Section: Literature Reviewmentioning
confidence: 99%